The Role of Hospital Image and Medical Service Quality on the Intention of Patients from the Riau Islands Province to Revisit Hospitals in Malaysia - Yunita Octaviani; Renza Fahlevi; Fitriana Aidnilla Sinambela (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
This study aims to analyze the effects of hospital image and perceived medical quality on trust and on revisit intention among patients from the Riau Islands Province who engage in medical tourism to Malaysia. This research employs a quantitative approach, using a survey method with questionnaires distributed to 120 respondents selected via purposive sampling. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results indicate that hospital image and perceived medical quality have a positive and significant effect on trust. Furthermore, trust is also found to have a positive and significant effect on revisit intention. These findings highlight that trust plays a crucial role in driving patient loyalty in medical tourism. This study implies that improving hospital image and medical service quality can strengthen patient trust, which ultimately enhances revisit intention.